Availability and utilization of e-learning facilities in the teaching of Senior School Physics in Ilorin, Nigeria - Abdulrasaq Oladimeji Akanbi (Journal of Education and Learning (EduLearn), 2020)
The study was intended to examine the utilization as well as the availability of E-learning facilities in the teaching of senior school physics in Ilorin, Nigeria. The study was a survey type and all physics teachers constitute the population. A total of 60 teachers was sampled for the study. Multi-stage sampling technique was adopted in the selection of respondents. Simple random sampling technique was used to select 20 out of 35 secondary schools. Two structured checklists were used to collect data. Percentage and mean were used to answer the research questions while ANOVA was used to test hypotheses at 0.05 level of significance. The finding revealed that printers, photocopying machine, desktop computers, laptop computers, Android phones, electronic typewriters and scanners were available, E-learning facilities were not utilized, there is no significant difference in the utilization of E-learning facilities for teaching physics based on teachers’ qualifications and experience. It was then recommended that physics teachers should be given proper training on how to use as well as maintain E-learning facilities in their various schools in order to equip them with the necessary skills, knowledge and values that will enable them optimize teaching in a fast changing world.